2023
DOI: 10.21203/rs.3.rs-2596388/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Assessment of the Microbial Quality of Food Contact Surfaces (Utensils) of Hotels and Restaurants in Addis Ababa

Abstract: Background: Food contact surfaces are surfaces that encounter food for humans. It can harbor and introduce pathogens into food. Objective: The aim of this study was to assess the microbiological quality of food contact surfaces (utensils) from hotels and restaurants in Addis Ababa. Methods: We used cross-sectional study design in which 12 hotels and 28 restaurants were randomly selected in Addis Ababa. Swab samples from utensils of hotels and restaurants were collected (i.e. four utensils from each establishme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 22 publications
1
1
1
Order By: Relevance
“…A study in Oman in Salalah state on food safety in restaurants found 1.6×10 5 CFU/cm 2 TPC count in food handlers' hand (Abdalla et al, 2015). Similar high counts were reported in restaurants provide RTE foods in Cairo, Egypt in hand and plate swab (Fahim et al, 2022), and in Addis Ababa, Ethiopia in plate, glass and food serving tray (Tenna et al, 2023). Our TVC values were somewhat lower compared to these studies but still high enough to introduce substantial contamination of the foods of these restaurants.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…A study in Oman in Salalah state on food safety in restaurants found 1.6×10 5 CFU/cm 2 TPC count in food handlers' hand (Abdalla et al, 2015). Similar high counts were reported in restaurants provide RTE foods in Cairo, Egypt in hand and plate swab (Fahim et al, 2022), and in Addis Ababa, Ethiopia in plate, glass and food serving tray (Tenna et al, 2023). Our TVC values were somewhat lower compared to these studies but still high enough to introduce substantial contamination of the foods of these restaurants.…”
Section: Discussionsupporting
confidence: 88%
“…Food contact surfaces that are not directly associated with food preparation but with serving and consumption have also been implicated to be contaminated with numerous microorganisms at higher levels like the cleaning clothes for the cleaning of serving tables or wiping plates, seating chairs and tables, serving trays, food holding spatulas, drinking glasses, and spoons (Patel et al, 2017;Giwa et al, 2021). An estimated 27% of outbreaks by foodborne pathogens are resulted from contaminated kitchen utensils, while 97% of foodborne illnesses are due to improper food handling practices in restaurants and at home (Tenna et al, 2023). In Bangladesh, many studies on knowledge, attitudes, practices, and training of restaurant workers, street vendors and other food service providers have reported poor to average knowledge level but serious lacking in training and hygiene practice, (Banna et al, 2022;Ali et al, 2023;Hashanuzzaman et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, other disinfectants could be more efficient, with lower toxicity, fast acting, and not be adversely affected by organic load, for the food industry in the removal of possible pathogenic microorganisms and improve hygienic conditions (Kim et al, 2023). The total coliform counts found in this study are lower than those found in the study of Tenna et al (2023), who evaluated the microbiological quality of food contact surfaces (utensils) from hotels and restaurants, and their counts ranged from 4.85 to 5.93 Log CFU/100 cm 2 . Total coliforms are considered indicators of failures in cleansing and disinfection procedures, which can represent cross contamination and biofilm formation on the surfaces.…”
Section: Resultscontrasting
confidence: 53%